Pneumatized articular tubercle and discontinuity of the temporal bone mandibular fossa: a computed tomographic study - Ferrer, Rosa; Hernández-Andara, Adalsa; Ortega-Pertuz, Ana Isabel (Revista Facultad de Odontología Universidad de Antioquia, 2019)
Introduction: air cells in the articular tubercle and the discontinuity of the cortical mandibular fossa are sites of minimal resistance, favoring the extension of various pathologies, which should be differentiated from similar processes involving bone expansion/destruction. The aim of this study was to assess pneumatized articular tubercle (PAT) and discontinuity of the temporal bone’s mandibular fossa (DMF) through computed tomography (CT), focusing on its distribution by age, sex, and laterality. Methods: 200 CT studies including both temporomandibular joints (TMJ) were selected, recording age, sex, presence/absence of PAT and DMF and their laterality. Results: 19% of patients had some anatomical variants. PAT was seen in 15.5% of cases (n = 31), 21 females (67.74%) and 10 males (32.26%). DMF was seen in seven cases (3.5%), all in females. 51.62% of PAT were bilateral, and 85.71% of DMF were unilateral. Conclusions: the sample under study has a high prevalence of PAT. DMF should be considered in the evaluation of TMJ by CT, with this being the method of choice to assess bone structures and air spaces in temporal bone.